(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this article, we delve into the intriguing concept of strongly geodesic log-preinvex functions in Riemannian manifolds. We present essential preliminaries and fundamental results that shed light on this specialized area of study. By examining the properties and implications of these functions, we aim to contribute to the growing body of knowledge in convexity theory within the context of Riemannian manifolds.